Effects of Parameters of Helmholtz Resonator on Transmission Loss of Hybrid Muffler - Zaw, Thiha; Abu, Aminudin; Fawazi, Noor; M. Wahab, A (International Journal of Engineering and Technology, 2018)
Expansion chamber and Helmholtz resonators are widely used in noise control. In this paper, they are combined to use as a hybrid muffler. The analysis is done to investigate the influence of the parameters of Helmholtz resonator on transmission loss. The transfer matrix method is used in the analysis. The result of transmission loss from the transfer matrix method is validated with the result from experimental two-load method using four microphones impedance tube. After had the transmission loss of the hybrid muffler been validated, the study was proceeded to investigate the effects of parameters of Helmholtz resonator on the transmission loss. The root mean square value of transmission loss were also calculated to compare the transmission losses clearly. In this paper, we investigated the effect of length of the neck of Helmholtz resonator, the effect of diameter of the neck of Helmholtz resonator, the effect of the length of the Helmholtz resonator cavity and the effect of the diameter of the Helmholtz resonator cavity for stationary medium. It is found that the transmission loss is increased when the diameter of the neck of Helmholtz resonator is increased. When the length of the neck is reduced, the transmission loss is increased. The transmission loss can also be increased by reducing the diameter of resonator cavity. It is better to increase the transmission loss at low frequencies by increasing the length of the resonator cavity.Â Â